2006
DOI: 10.1080/09712119.2006.9706609
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Rennet Type on the Texture and Colour of Goats Cheese

Abstract: Goat milk cheese was made using natural rennet paste from kid's abomasum using the traditional method used for Palmero AOC Cheese and commercial rennet (50% quimosin, 50% pepsin). Changes in composition, colour and texture were evaluated in fresh (6d ripening), semi-hard (40d ripening) and hard cheeses (70d ripening) that were made according to the specifications of AOC Regulatory Board. Cheese made with natural paste were harder, more elastic, breakable and darker than those made with commercial rennet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 7 publications
5
19
0
Order By: Relevance
“…Madadlou et al (2005) reported that doubling the rennet concentration in LFC improved the rheological properties and sensory impression of texture, as well as increasing meltability in Iranian white cheese. Using natural rennet (Fresno et al 2006) can be another alternative to improve the quality of low-fat goat cheese. As fat is removed from the cheese milk, cheese-making procedures that are generally used for manufacturing FFC should be modified to correct the associated textural and flavour defects, including improving moisture retention and reducing acid accumulation.…”
Section: Journal Of Applied Animal Research 129mentioning
confidence: 99%
“…Madadlou et al (2005) reported that doubling the rennet concentration in LFC improved the rheological properties and sensory impression of texture, as well as increasing meltability in Iranian white cheese. Using natural rennet (Fresno et al 2006) can be another alternative to improve the quality of low-fat goat cheese. As fat is removed from the cheese milk, cheese-making procedures that are generally used for manufacturing FFC should be modified to correct the associated textural and flavour defects, including improving moisture retention and reducing acid accumulation.…”
Section: Journal Of Applied Animal Research 129mentioning
confidence: 99%
“…A similar observation was made by Khosrowshahi et al [2006] in Iranian white cheese during ripening. According to Fresno et al [2006], many biochemical modifi cations occur in the maturation process of cheeses. Van Boekel [1998] reported that modifi cations in lactose due to series of reactions result in brown pigmented products such as pyrazines and melanoidins, and small acid molecules are also formed during the Maillard reaction.…”
Section: Colour Parametersmentioning
confidence: 99%
“…For example, GCRC1 and GCRC2 acknowledged that, overall, the GCRC oversees the fulfillment of prescribed food-related regulatory requirements, ranging from ensuring farmers' compliance with the selected type of goat feed, including grazing sites to pasture, to the use of commercial or "artisan" goat kid rennet paste (Fresno et al, 2006) as a coagulant to curdle goat milk. GCRC representatives also oversee the proper organization and maintenance of the farming operations, including observation of compliance with hygiene standards during the cheese-making process.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, since the 1990s, as many as 10 wine regulatory councils have been established in the local wine sector, which in recent decades has experienced a revival based on the increasing professionalization occurring at many of the local wineries (Alonso & Liu, 2012). In the cheese sector, to date, three regulatory councils of Protected Designations of Origin (PDOs) have been established in as many islands, the first in Fuerteventura in 1996 (Álvarez, Calero, Fernández, Fresno, & González, 2009), the second in La Palma in 2002 (Fresno, Álvarez, Rodríguez, Castro, & Argüello, 2006), and the most recent (2009) in Gran Canaria (González-Sosa, 2009). …”
Section: Introductionmentioning
confidence: 98%